2009
DOI: 10.1002/jccs.200900061
|View full text |Cite
|
Sign up to set email alerts
|

Mild Oxidation of Oxime Derivatives with KMnO4 in Ionic Liquid Media

Abstract: In this research, potassium permanganate in the presence of a catalytic amount of [bmim]Br under solvent free conditions is used as an efficient and chemoselective method for oxidative cleavage of some oximes to corresponding carbonyl compounds. This experiment was carried out in mild conditions without any further oxidation of aldehydes to corresponding acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[36][37][38] In the continuation of ongoing studies on the application of IL media, it was found that dialkylimidazolium halide derivatives have many advantages over conventional solvents. [39][40][41][42] These reagents are safe, easy to handle, environmenttally benign and present fewer disposal problems. Therefore, butylmethylimidazolium bromide ([bmim]Br) (Scheme 1) could be an excellent candidate for employment in organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] In the continuation of ongoing studies on the application of IL media, it was found that dialkylimidazolium halide derivatives have many advantages over conventional solvents. [39][40][41][42] These reagents are safe, easy to handle, environmenttally benign and present fewer disposal problems. Therefore, butylmethylimidazolium bromide ([bmim]Br) (Scheme 1) could be an excellent candidate for employment in organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…This cyclization reaction of hydroxylamine and chalcone provided isoxazoline derivatives in the ionic liquid butylmethylimidazolium bromide as a catalyst (Scheme 29). [71] Results displayed that IL media, i. e., dialkylimidazolium halide derivatives, have several advantages in comparison to the traditional solvents [67–70] . So [bmim]Br was found to be an excellent catalyst to be used in organic synthesis because it enhances higher selectivity, reaction rates, cleaner products, and simplicity in contrast to the traditional procedures.…”
Section: Five‐membered Heterocycle Having Nitrogen and Oxygen Atomsmentioning
confidence: 99%
“…Safaei-Ghomi and Hajipour 281 investigated the oxidative cleavage of some oximes with KMnO 4 as oxidant in the presence of [BMIM][Br] under solvent-free conditions. Yields above 81% could be obtained with an oxime:IL:KMnO 4 ratio of 1:0.7:1.4 at room temperature without any further oxidation of aldehydes to acids.…”
Section: Oxidation Of Oximesmentioning
confidence: 99%